STRATEGI PERBANKAN SYARIAH DALAM MENYOKONG INDONESIA MENJADI TREND SETTER INDUSTRI HALAL - Yustati, Herlina; Handayani, Disfa Lidian (Jurnal BAABU AL-ILMI: Ekonomi dan Perbankan Syariah, 2017)
Abstract: This paper is the result of research on several literatures encountered to provide solutions how the strategy that can be applied by sharia banking that started developing in Indonesia in developing halal industry in Indonesia. Indonesia is a country with the largest Muslim majority in the world. Muslims are a potential market in developing the current halal industry. Because Islam regulates every aspect of human life especially from the consumption sector. Consumption is broadly defined as utilizing every product. There are four major sectors which are great opportunities in developing halal industry namely, food industry, pharmaceutical industry, fashion industry and tourism industry. Islamic banking can have a role in developing the four sectors, including Cooperation with companies that will issue products with halal labeling to financially use sharia banking, syariah banking can develop sharia debit card and sharia card to facilitate the tourists to access youth syariah tourism, sharah perbnakan can provide financing for entrepreneurs in the field of syariah tourism, fashion and pharmaceutical products to develop their business which ultimately helped improve the halal industry in Indonesia.Keywords:  Halal Industry, Sharia Bank